Pengaruh Model Pembelajaran Discovery Learning Berbantuan Video Pembelajaran Interaktif terhadap Kemampuan Kognitif Siswa MA Ummul Mukminin - Hamsyah, Eka Fitriana; Gustina, Gustina; Ahmad, Fandi (Jurnal Kreatif Online, 2020)
This study aims to determine the effect of the discovery learning model assisted by interactive learning videos on the cognitive abilities of MA Ummul Mukminin students. The research design was a one group pretest-postest design. The population of this research was all students of class XI MA Ummul Mukminin. The sample in this study was chosen randomly. The instrument used to measure students' cognitive abilities was in the form of multiple-choice questions of 20 numbers given at the pretest and posttest. The data analyzed by descriptive statistical analysis and inferential statistical analysis. Inferential statistical analysis consisted of normality test, homogeneity test, and hypothesis test. Hypothesis testing used the help of the SPSS For Windows 17.0 application through the Paired Sample t-test. The test results obtained a significance value of 0.000 <0.005, which means that there was a significant effect of using the discovery learning model assisted by interactive learning videos in improving the cognitive abilities of MA Ummul Mukminin's students.